Dissimilar of Customer Perception and Expectation Among Rural and Urban Markets - Shanthakumari, Dr. S.S. Shanthakumari; Kannan, P. (Journal of Contemporary Research in Management (JCRM), 2013)
This paper will be focusing on the dissimilarities between rural and urban customer expectation and perception. The reasons are India lives in villages, close to 72 percent of Indian population live in rural areas. The rural economy contributes nearly half of the country’s GDP which is mainly agriculture driven and monsoon dependant. More than 50 percent of the sales of FMCG and Durable companies come from the rural areas. Now-a-days a lot of service sectors are entering into rural market like banking, telecommunication, insurance, healthcare etc., Service quality measurements start with measuring the perception and expectation. The gap between expectation and perception of customers for different service dimensions were identified. Customer satisfaction and loyalty as a consequence of high quality provides a long term survival and success. In order to survive and have a long- term relationship with customers, understanding them, meeting their expectations and being different from rural and urban aspects should be focuses on. The concept of customer expectation and perception has received considerably high attention. Many ervice providers develop long-term relationships with clients where both the parties accumulate experience with each other. There is a gap between the customer expectation and service quality offered in urban and rural areas. It leads to a shift in the customer preference from one service provider to other parties. There is a need to identify the gap between rural and urban customer perception and expectation. This study will prove the dissimilarities of expectations and perceptions among the rural and urban customers.